SISTEMA PARA MEJORAR LA ESTABILIDAD DE LOS MOTORES DIESEL EN REGIMENES DE BAJAS CARGAS Y VELOCIDADES - Lira Cacho, Guillermo (2018)
This work presents a system to improve stability of diesel engines in low loads and rotational speed rates by using a special and easy valve, called RND, which is installed in the high pressure pipe. This valve is actioned automatically by pressure difference, which lets insert low fuel quantities directly to the line, making the injection process steady in the indicated rates. Comparative results of the test made in a linear injection pump are included, to which a RND valve and a piezoelectric sensor was installed. The oscilograms of pressure and the inequality of fuel supply, in order to determine the improvement of stability of the injection system performance, are also included.